2008
DOI: 10.1902/jop.2008.080210
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Glycation of Type I Collagen and Fibronectin Modifies Periodontal Cell Behavior

Abstract: Background: Advanced glycation end products (AGEs) have been linked to pathogenic mechanisms of diabetes mellitus. However, little is known about the contribution of protein glycation to periodontal disease in patients with diabetes. Therefore, this study investigated whether glycation of type I collagen (COLI) and fibronectin (FN) modified the behavior of human gingival fibroblasts (hGF) and periodontal ligament fibroblasts (hPDL).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 54 publications
1
37
1
1
Order By: Relevance
“…50 Fibronectin in diabetic humans is subject to advanced glycation end products (AGE) that can affect fibronectin structure and function. 51 AGE-modified fibronectin has reduced ability to support cell adhesion, spreading, and migration, 52,53 and to bind to collagen and heparin. 54 As such, the fibronectin fibrils observed in uninjured human diabetic skin may have reduced function.…”
Section: Discussionmentioning
confidence: 99%
“…50 Fibronectin in diabetic humans is subject to advanced glycation end products (AGE) that can affect fibronectin structure and function. 51 AGE-modified fibronectin has reduced ability to support cell adhesion, spreading, and migration, 52,53 and to bind to collagen and heparin. 54 As such, the fibronectin fibrils observed in uninjured human diabetic skin may have reduced function.…”
Section: Discussionmentioning
confidence: 99%
“…However, abnormal differentiation or function of myofibroblasts has been associated with delayed or pathologic wound repair 15 , 17 . A number of studies have analyzed the effect of glycated collagen on connective tissue cells of the myocardium and periodontium 3,11,18,29 . Culture of human cardiac fibroblasts over glycated collagen stimulates differentiation of myofibroblasts through involvement of TGF‐β2 and collagen‐binding integrin α11β1 18 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…The sequence GFOGER is the principal collagen‐binding domain recognized by integrins in Type I collagen 9 . More specific studies have identified that MGO modifies the arginine residue present in this sequence, altering the interaction between glycated collagen and gingival fibroblasts delaying cell migration and collagen remodeling 10 , 11 . Moreover, soluble MGO induces apoptosis in gingival fibroblasts, reducing the number of cells available for wound healing 12 .…”
mentioning
confidence: 99%
“…[13][14][15][16] Some authors 1,2 have stated that it remains a relative contraindication for implant treatment, while others 3,4 that survival of implants could be improved if plasma glucose concentrations were brought under control. In our previous study 11 our results suggested the latter point of view, and we found that survival of implants could be improved in diabetic subjects when plasma glucose concentrations were controlled.…”
Section: Discussionmentioning
confidence: 99%